Perspectives on Organizational Communications: Finding Common GroundPerspectives on Organizational Communication: Finding Common Ground, edited by CormanSteven R. and PooleMarshall Scott. New York: Guilford Press, 2000. - Ashcraft, Karen Lee (Academy of Management Review, 2001)
The article reviews the book ?Perspectives on Organizational Communication: Finding Common Ground,? edited by Steven R. Corman and Marshall Scott Poole.